Application of advanced oxidation processes for effective Reactive Red 241 degradation - Barbara Pieczykolan; Izabela Płonka; Edyta Kudlek; Rafał Kryst; Patrycja Stuchlik; Dominika Pokoj; Karolina Hanzlik; Nikodem Piekarczyk; Igor Orłowski; Martyna Grodzicka (Desalination and Water Treatment, 2025)
Advanced oxidation processes (AOPs) were investigated for the Reactive Red 241 (RR 241) degradation in aqueous solutions. Nine different methods were tested: the Fenton process, Fenton combined with Sodium Percarbonate (Fenton-SP), Fenton with MgO₂ (Fenton-MgO₂), and the UV/TiO₂ process utilizing both low-pressure (LPL) and medium-pressure (MPL) lamps. Additionally, the methods included UV(MPL)/H₂O₂, UV(MPL)/Fenton, and UV(MPL)/Fenton-like processes. For each method, optimal conditions (pH, reaction time, and reagent dosages) were identified. The dye concentrations in the treated solutions were as follows: 0.67 mg/dm³ for the Fenton process, 0.73 mg/dm³ for Fenton-SP, and 0.83 mg/dm³ for Fenton-MgO₂. The UV(MPL)/Fenton-MgO₂ method achieved a degradation efficiency comparable to the Fenton process. Among all the methods tested, the highest degradation efficiency of RR 241 was achieved using the UV(MPL)/H₂O₂ process, which reduced the dye concentration to 0.53 mg/dm³ . Conversely, the lowest degradation efficiency was recorded in the UV(LPL)/TiO₂ process, where the dye concentration was 4.09 mg/dm³ . Chromatographic analysis confirmed the presence of RR 241 intermediates. The highest number of these intermediates was observed with the UV(MPL)/TiO₂ process, likely due to its broader wavelength range and higher light intensity. In contrast, the UV(MPL)/Fenton processes resulted in the lowest number of by-products, indicating more complete mineralization.